Isolation of chemical compounds and essential oil from agrimonia asiatica juz. And their antimicrobial and antiplasmodial activities (2020)
Agrimonia asiatica is a perennial plant with deep green color and covered with soft hairs and has a slightly aromatic odor. +is genus Agrimonia has been used in traditional medicines of China, Greece, and European countries. It was mainly used as a haemostatic, a tonic for asthenia, and an astringent for diarrhea. Agrimony is part of the division Magnoliophyta; class is represented by order Rosales, family Rosaceae, of the genus Agrimonia. Family Rosaceae—or pink eels—is one of the largest families of flowering plants, including about 100 genera and 3000 species. Rosaceae is common in almost all areas of the globe where flowering plants can grow, but most of them are concentrated in the temperate and subtropical zones of the Northern Hemisphere. Phytochemical investigation on ethanolic extract of A. asiatica led to isolation of four flavonoid derivatives (kaempferol-3-glycoside, quercetin-3-O-α-arabinofuranosyl-β-D-galactopyranoside, 3-O-kaempherol 2,3-di-O-acetyl-4-O-(cis p-coumaroyl)-6-O-(trans-p-coumaroyl)-β-D-glucosopyranoside, and catechin) alongside of sucrose. All the extracts, fractions, and isolated compounds were tested for antimicrobial and antiplasmodial activities. We also studied the chemical composition of essential oil obtained from the aerial part of A. asiatica. +e essential oil constituents from the aerial part of A. asiatica were obtained using a steam-distillation method in wild growing conditions in Kazakhstan. +e essential oil extracted from the aerial part of the plant was analyzed by gas chromatography-mass spectroscopy and its major components amounting to 100% were found to be β-selinene (36.370%), α-panasinsene (21.720%), hexadecanoic acid (7.839%), and 1,2-nonadiene (6.199%). Neither the extract nor the isolated compounds showed antimicrobial and antiplasmodial activities.